Old Yaws Hospital - (:unkn) unknown (My University, 2009)
Front entrance of Old Yaws Hospital, as it was turned over to the College - March 1922
Black and white photograph.
Keywords: ICTA; Imperial College of Tropical Agriculture; Buildings; Yaw Hospital